Impact of Cold Exposure on the Reproductive Function in Female Rats. (22nd November 2018) - Xu, Tong; Li, Xi; Yang, Lin; Zhang, Yongqiang; Zhang, Li; Guo, Zhan; Cheng, Xiaodan; Zheng, Xiantong; Chen, Baodong; Hou, Zhidong; Yang, Danfeng
Abstract : Female reproductive system diseases caused by exposure to a cold environment are widely considered as important human health challenges. Although the projection of female reproduction in cold temperature has been studied, a holistic view on the probable effects of cold exposure on the functions of the female reproductive system has not been achieved. Our aim was to evaluate the effects of cold exposure to the functions of the ovary and uterus in female rats. For this purpose, female rats were randomly grouped as follows: (1) the cold group was exposed to -10°C, 4 h per day for 2 weeks, and (2) the normal temperature (23 ± 1°C) group was used as control. Alterations were observed in different parameters, including body weight gain, organ coefficients, estrus cycle, and pathology of the cold-exposed female rats. Similarly, the serum reproductive hormones and mRNA expression were evaluated. Cold exposure induced estrus cycle irregularity and some alterations in the morphology of the ovary. Cold exposure impairs the function of the ovary probably by changing the level of serum LH and increasing LHR expression. Cold exposure induced a significant reduction of uterine epithelium height. Cold exposure causes alterations in the morphology of the uterus probably because of the effect of progesterone, the increase in the PR level, and the decrease in the ER level.